1977
DOI: 10.1121/1.381278
|View full text |Cite
|
Sign up to set email alerts
|

Intensity discrimination as a function of frequency and sensation level

Abstract: Intensity discrimination was measured for pulsed sinusoids of various frequencies (200–8000 Hz) and sensation levels (5–80 dB). The data for all frequencies were fitted by a single function, ΔI/I=0.463 (I/I0)−0.072, where I0 is intensity at threshold, I is the intensity of the tone, and ΔI is the increment needed to obtain 71% correct in a two-interval forced-choice adaptive procedure. The form of this function is in good agreement with data reported in comparable studies but differs markedly from the data rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
150
5
1

Year Published

1989
1989
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 355 publications
(177 citation statements)
references
References 0 publications
21
150
5
1
Order By: Relevance
“…All these results together exhibit the same general trend and appear quite consistent with one another. The absolute size of the M.s, between 0.3 and 0.7 dB, agree quite well with intensity DLs measured with l000-Hz tones and welltrained subjects (Jesteadt, Wier, & Green, 1977;Rabinowitz, Lim, Braida, & Durlach, 1976).…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…All these results together exhibit the same general trend and appear quite consistent with one another. The absolute size of the M.s, between 0.3 and 0.7 dB, agree quite well with intensity DLs measured with l000-Hz tones and welltrained subjects (Jesteadt, Wier, & Green, 1977;Rabinowitz, Lim, Braida, & Durlach, 1976).…”
Section: Resultssupporting
confidence: 70%
“…when T increases from 10 to 20 msec, then decreases much less rapidly or remains rather constant for Tvalues between 20 and 40 msec. This is equivalent to the socalled near miss to Weber's law reported in the literature for intensity discrimination of pure tones (Jesteadt et al, 1977). There are several possible reasons for the differences between our results, shown in Figure 8, and those of Henning (1970) and Florentine (1986).…”
Section: Resultscontrasting
confidence: 53%
“…Thus, pairs of stimuli, equally spaced in decibels should be equally discriminable (Weber's law). Because Weber's law does not hold for pure tones (e.g., Jesteadt, Wier, & Green, 1977), Braida and Durlach (1972) argue that a logarithmic mapping should be considered as a first-order approximation to a(I ). When they reanalyzed their data after correcting for the near-miss to Weber's law, they concluded that a better approximation to a(I ) is (3) where I 0 is the threshold intensity.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, signal-in-noise (segmentation) and fine (feature discrimination) paradigms have been used widely to study sensory processing in both human and nonhuman primates (e.g., Hawkins and Stevens, 1950;Jesteadt et al, 1977;Orban et al, 1984;Newsome and Paré, 1988). Achieving a clear understanding of the benefits of training on such tasks has implications that extend to sensory rehabilitation (Green and Bavelier, 2003, 2006a, 2006bLi et al, 2009).…”
Section: Generalization Across Image Featuresmentioning
confidence: 99%